Al-Mar’ah fi al-Qur’ân ‘Inda Ibn ‘Asyûr fi Tafsîrih (Dirâsah ad-Dilâlah al-Qur’âniyyah) - Ali Mahfuz Munawar; Dyah Nurul Azizah (Universitas Darussalam Gontor, 2017)
Al-Mar’ah in the Qur’an was one of the main discussions among Muslim scholars and mufassirin, either seen from the position level or the role of their life. There are various studies about Al-Mar’ah in the Qur’an, also the term that is used for the context of mar’ah, they are “imro’ah and nisa’. Centuries ago, a large number of orientalist placed the Qur’an as the main study, which had never been separated from jewish analogy. In fact, the most muslims had been incited by their digression of thought. So, the prominent Muslim scholar and the contemporary mufassir, Ibnu’Asyur tried to straighten the anconformity assumption of orientalist in accordance to the Divine Revalation of God and Islamic teaching. Ibnu ‘Asyur’s thought about “imro’ah and nisa” according to the semantic Qur’an study based on dalil naqly and aqly on his tafsir. Thus, the interpretation is very oriented to the study of language depth. The term